(untitled) (Belmont, CA., 2004)
This two-semester textbook introduces the principles, techniques, and laboratory skills that are used in modern chemical analysis. The included CD-ROM contains tutorials and guided simulations. The eighth edition adds chapters on sampling and calibration and the use of spreadsheets.
Keywords: Chemistry, analytic